Graduates’ perception of the relationship between technical and vocational education and training and graduates’ employment prospects - Awal, Rabiul (Journal of Management and Business Education, 2025)
Industrialization and modernization have raised demand for skilled workers in many fields. Government and other institutions have promoted Technical and Vocational Education and Training (TVET) programmes to meet this demand by providing job-ready skills and knowledge. Despite these efforts, there are concerns about the effectiveness of TVET in terms of graduate employment prospects in Bangladesh. A clear understanding of TVET graduates' attitudes and experiences is essential to improving TVET effectiveness. The online survey data from these graduates provided valuable insights into their learning, skill development, and employment outcomes. Data was acquired from 152 respondents (n = 152) using convenience sampling and snowball sampling techniques. This study analysed the acquired data using descriptive statistics, factor analysis, and a multiple regression model in the SPSS programme. According to the findings, TVET graduates have an overwhelming perception of a positive relationship between TVET programmes and their employment prospects. The current study also identified two main aspects or factors, namely the 'skills development factor' and the 'employment benefits factor,' which can influence TVET graduates' perceptions. However, of these two components, the skills development aspect has a very high and significant impact on graduates' perceptions, while the employment benefits factor has no statistical effect.